Comparison of Urgency, Weak Stream, Incomplete Emptying and Nocturia Score with International Prostate Symptom Score in Symptomatic Men with Benign Enlargement of Prostate - Thakur, Dipak; Pradhan, Manish Man; Poudyal, Sujeet; Subedi, Pradip Prasad; Chapagain, Suman; Luitel, Bhoj Raj; Gupta, Dipesh Kumar; Chalise, Pawan Raj; Sharma, Uttam Kumar; Gyawali, Prem Raj (Birat Journal of Health Sciences, 2025)
Introduction: Assessment of lower urinary tract symptoms (LUTS) in benign enlargement of prostate (BEP) patients is necessary to initiate and assess treatment. International Prostate Symptom Score (IPSS) is common, but it takes time and many patients have difficulty in understanding. A new score-Urgency, Weak Stream, Incomplete Emptying and Nocturia (UWIN Score), presumed to be easier and well understood has been introduced. Objectives: The aim of the study was to compare UWIN Score with the IPSS in symptomatic men with BEP in our institution. Methodology: In this cross-sectional study, 40 patients with LUTS diagnosed with BEP clinically, were enrolled. Symptom evaluation was done in all with both UWIN score and IPSS. The UWIN score and IPSS were compared with each other and with prostate volume. Results: The mean age and prostate volume were 67±8.9 years and 46±19.5 gm respectively. Time taken and assistance required to complete UWIN score was significantly less (p=< 0.001) compared to IPSS. Total UWIN score correlated with total IPSS (ρ= +0.77; p=<0.001). The Quality of life( QoL ) domain of UWIN score also correlated with QoL domain of IPSS (ρ=0.542; p=<0.001). There was no correlation of both UWIN score (ρ=0.15) and IPSS (ρ=0.03) with prostate size. Conclusion: UWIN score was equally effective as IPSS in assessing LUTS in symptomatic men with BEP. UWIN score was easier to understand, fast, requiring lesser help even in patients with poor educational status.